2022
DOI: 10.48550/arxiv.2201.03571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New constraints on the dark matter density profiles of dwarf galaxies from proper motions of globular cluster streams

Abstract: The central density profiles in low-mass and dwarf galaxy halos depend strongly on the nature of dark matter. Recently, in Malhan et al. (2021), we employed N-body simulations to show that the cuspy cold dark matter (CDM) subhalos predicted by cosmological simulations can be differentiated from cored subhalos using the properties of accreted globular cluster streams -those stellar streams produced from the tidal stripping of globular clusters that initially evolved within their parent dwarf galaxies and only l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Cocoons, spurs and gaps have now been detected with Gaia photometry and proper-motions in several GC streams [121,122]. It has been shown recently that quantities that measure the "hottness" of accreted GC tidal streams (physical width, line-of-sight velocity dispersion, tangential velocity dispersion, and angular momentum spread) are sensitive to whether the parent satellite from which the GC was accreted had a cuspy or cored dark matter halo [119,123]. These simulations have found that stellar streams formed in cored DM halos are systematically narrower (in physical width) and have lower velocity dispersion (both lineof-sight and tangential) than those formed in cuspy halos [119,123].…”
Section: Constraints On Dark Matter Subhalos From Stellar Tidal Streamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocoons, spurs and gaps have now been detected with Gaia photometry and proper-motions in several GC streams [121,122]. It has been shown recently that quantities that measure the "hottness" of accreted GC tidal streams (physical width, line-of-sight velocity dispersion, tangential velocity dispersion, and angular momentum spread) are sensitive to whether the parent satellite from which the GC was accreted had a cuspy or cored dark matter halo [119,123]. These simulations have found that stellar streams formed in cored DM halos are systematically narrower (in physical width) and have lower velocity dispersion (both lineof-sight and tangential) than those formed in cuspy halos [119,123].…”
Section: Constraints On Dark Matter Subhalos From Stellar Tidal Streamsmentioning
confidence: 99%
“…It has been shown recently that quantities that measure the "hottness" of accreted GC tidal streams (physical width, line-of-sight velocity dispersion, tangential velocity dispersion, and angular momentum spread) are sensitive to whether the parent satellite from which the GC was accreted had a cuspy or cored dark matter halo [119,123]. These simulations have found that stellar streams formed in cored DM halos are systematically narrower (in physical width) and have lower velocity dispersion (both lineof-sight and tangential) than those formed in cuspy halos [119,123]. A comparison of simulations with existing Gaia proper motions in about 7 streams already imply that many observed GC streams are too cold to be consistent with formation in cuspy CDM halos of mass 10 9 M ⊙ .…”
Section: Constraints On Dark Matter Subhalos From Stellar Tidal Streamsmentioning
confidence: 99%